ПРОВЕРКА КАК ФОРМА КОНТРОЛЯ ЗА АДВОКАТСКОЙ ДЕЯТЕЛЬНОСТЬЮ - Файнгольд, Ирэна Давыдовна (SUPREMANCE OF LAW, 2017)
The forms of realization of administrative powers by subjects of control in the field of advocacy are being investigated. The article focuses on the study of such a form of control as verification, in particular, the relevant competence of the qualification and disciplinary commissions of the bar, the quality assessment commissions, the completeness and timeliness of legal aid by lawyers, the bodies of the justice system (Gosfinmonitoring). According to the results of the research, the author singled out separate administrative verification procedures as a form of control.
Keywords: advocacy; verification; control; procedure